Redescription of Aspidosiphon (Paraspidosiphon) steenstrupii Diesing, 1859 (Sipuncula: Aspidosiphonidae) and the reinstatement of three species - Itzahi Silva-Morales; Luis F. Carrera-Parra (PeerJ)
Sipuncula, specifically the family Aspidosiphonidae, faces taxonomic challenges due to brief original descriptions and the poor condition or loss of the type material. Detailed standardized redescriptions are essential to understanding the diversification in this group. Herein, a comprehensive redescription of Aspidosiphon (Paraspidosiphon) steenstrupii based on an extensive material collection from the tropical Western Atlantic is provided. Based on morphological data and the analysis of COI sequences, we delimited A. (P.) steenstrupii morphologically, restricting its distribution to the tropical Western Atlantic. Also, the redescriptions and proposals for reinstatement of A. (P.) exostomum, A. (P.) ochrus, and A. (P.) speculator, previously considered junior synonyms of A. (P.) steenstrupii, are included. Furthermore, a comprehensive discussion on diagnostic morphological features to recognize aspidosiphonid species and a detailed revision of synonyms of A. (P.) steenstrupii are included. Notable differences in morphology and genetic data suggest the need for revising the taxonomic status of several synonyms within the family, highlighting underestimated diversity in sipunculans.